Peripheral Blood Count Characteristics, Neutrophil-Lymphocyte Ratio, and Platelet-Lymphocyte Ratio Pulmonary Tuberculosis Patients with Depression - Shatri, Hamzah; Alexander, Reinaldo; Putranto, Rudi; Rumende, Cleopas Martin (Jurnal Penyakit Dalam Indonesia, 2019)
Introduction. Patients with pulmonary tuberculosis (TB) had an increased risk for depression up to 1.53 times from a large cohort study. Studies have found an increase in the neutrophil - lymphocyte ratio (NLR) in various mood disorders including depression, also the value of the platelet-lymphocyte ratio (PLR) associated with major depression accompanied by psychotic symptoms. This study aimed to describe the peripheral blood characteristics, NLR, and PLR in pulmonary TB patients with depression. Methods. A cross-sectional study of 106 non-multidrug-resistant pulmonary TB patients was done at outpatient department of Cipto Mangunkusumo General Hospital, Jakarta from August to October 2018. The diagnosis of depression was made by interview according to Diagnostic and Statistical Manual of Mental Disorder-V (DSM-V) criteria, and severity of depression is determined using Beck Depression Inventory-II (BDI-II). The laboratory tests were done to obtain complete peripheral blood results, NLR, and TLR. Parametric test was used for numeric variables with even distribution, and nonparametric test for variables with uneven distribution. Results. From 106 patients with non-multidrug-resistant pulmonary TB, the proportion of depression was 32%. White blood cell count (p=0.024), and absolute lymphocte count (p=0.004) is lower in depressed TB patients compared to nondepressed TB patients. There were no significant relationship between NLR and TLR and the severity of depression in depressed pulmonary TB patients (p>0.05). Conclusion. White blood cell count and absolute lymphocyte count are lower in depressed pulmonary TB patients. Meanwhile, RNL and PLR are higher in depressed pulmonary TB patients eventhough not statistically significant.